The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1007/bf00234527
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Na-K-Cl cotransport in alveolar epithelial cells: Effect of phorbol ester and osmotic stress

Abstract: We have investigated the presence of Na-K-Cl cotransport in alveolar type II cells using uptake of 86Rb. Several data support the presence of a Na-K-Cl cotransport in these cells. First, a large fraction of ouabain-resistant 86Rb uptake was inhibited by bumetanide and furosemide. Second, bumetanide-sensitive 86Rb uptake required the presence of Na+ and Cl- in the incubation medium; dependency on extracellular Na+ and K+ was hyperbolic, with a Km of 14.6 mM and 8.3 mM, respectively, while dependency on extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Recent studies using T84 cells suggested -myoinositol 3,4,5,6-tetrakisphosphate (Ins(3,4,5,6)P % ) as a negative messenger in blocking Ca# + -regulated Cl − channels following the rise in intracellular Ca# + level (Ismailov et al, 1996 ;Vajanaphanich et al, 1994). Furthermore, PMA has also been shown to down regulate the basolateral Na + -K + -ATPase (Beron et al, 1997) and Na + -(K + )-2Cl − cotransporter (Clerici et al, 1995) in A6 and alveolar epithelia, respectively. These factors may also contribute to the down regulation of Cl − secretion after maximal stimulation induced by PMA.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies using T84 cells suggested -myoinositol 3,4,5,6-tetrakisphosphate (Ins(3,4,5,6)P % ) as a negative messenger in blocking Ca# + -regulated Cl − channels following the rise in intracellular Ca# + level (Ismailov et al, 1996 ;Vajanaphanich et al, 1994). Furthermore, PMA has also been shown to down regulate the basolateral Na + -K + -ATPase (Beron et al, 1997) and Na + -(K + )-2Cl − cotransporter (Clerici et al, 1995) in A6 and alveolar epithelia, respectively. These factors may also contribute to the down regulation of Cl − secretion after maximal stimulation induced by PMA.…”
Section: Discussionmentioning
confidence: 97%
“…acids (Clerici et al, 1990) and Na+-K'-2Cl- (Clerici et al, 1995), and is extruded across the basolateral side by a Na+, K'-ATPase. However, the use of primary cultures for AT11 studies is restricted by: (1) early dedifferentiation: within a few days, surfactant secretion decreases, cell surface binding characteristics change and Na' transport drops (Yue et al, 1993); and (2) heterogeneity of the material obtained through enzymatic digestion: AT11 are contaminated by macrophages and fibroblasts, which may interfere with measurement of transport.…”
mentioning
confidence: 99%
“…Clearly, the response of alveolar epithelial cells to hypotonic shock is different from that of kidney cells which have to adapt their ionic transport to the changing tonicity of the tubular environment. Some studies have reported changes in Rb + uptake in response to different tonicity challenges in alveolar epithelial cells [44]. To the best of our knowledge, the present investigation is the first to describe the impact of hypotonicity on transepithelial current generated in rat alveolar epithelial cells.…”
Section: Discussionmentioning
confidence: 76%